THE INFLUENCE OF MANAGEMENT DISCUSSION AND ANALYSIS (MD&A) ON INVESTOR REACTIONS FROM AN ISLAMIC ECONOMIC PERSPECTIVE (Study of Food and Beverage Companies Registered in BEI Period 2020-2022) - Kurniawan, Agus; Saputra, Leo; Mustofa, Ulul Azmi (FIDUSIA : JURNAL KEUANGAN DAN PERBANKAN, 2024)
MD&A (Management Discussion and Analysis) is part of a company's annual report where management provides analysis and explanation of the company's financial performance and risks. It is an important part of financial reporting as it allows gaining insight into a company's operations and decisionmaking processes. Indications of investor reactions are influenced by internal company factors, namely Management discussion and analysis. This research aims to determine the influence of Management discussion and analysis on Investor Reactions in Stock Returns and Trading Volume Activity. The type of research used is associative quantitative research. The data collection technique used is documentation. The population of this research is 18 food and beverage companies listed on the Indonesian Stock Exchange (BEI) in the 2020-2022 period. The sampling technique used was purposive sampling, and the total sample obtained was 45 data sourced from 15 company annual reports. The data analysis technique used in this research is panel data regression analysis with the help of eviews 12 software The research results show that Y1, it can be concluded that Management discussion and analysis has no significant effect on Stock Returns in food and beverage companies listed on the IDX in 2020-2022. And Y2 Management discussion and analysis has no effect on Trading Volume Activity in food and beverage companies listed on the IDX in 2020-2022. Keywords: Management discussion and analysis (MD&A), Return on equity (ROE) and Debt To Equity Ratio (DER), Stock Returns, Trading Volume Activity